Preliminary Characterization of Dog Derived Pathogenic Strains of Leptospira interrogans Serovar Australis in Nanchang of Jiangxi Province, China - Song, Ning; Zhang, Wenlong; Ding, Yue; Wu, Dianjun; Dai, Zonghao; Xu, Li; Cao, Yongguo (Frontiers in Veterinary Science, 2021)
Leptospirosis, induced by pathogenic leptospira, is a global zoonotic disease. In-fected animals show a variety of clinical symptoms and even death. The discovery of endemic strains is important for the production of effective vaccines. In this study, a strain of Leptospira was isolated from dog in Nanchang, Jiangxi Province, China. Using MLST analysis, the serovar of isolated Leptospira was identified and belonged to Leptospira interrogans serovar Australis. Then, the virulence of this strain was studied by using hamsters. After infection, all the hamsters have died within 4-5 days. Typical pathological changes were found in the liver, kidney, and lung of ham-sters. These results indicated that the isolated leptospira was pathogenic. This study helps to identify local Leptospira strains, and develop a more targeted canine leptospira vaccine.